Polyamorous Parenting: Stigma, Social Regulation, and Queer Bonds of Resistance. (December 2019) - Klesse, Christian
As a response to the greater visibility of alternative relationship and family forms, polyamory (i.e. the practice of consensual multipartner relationships) has recently moved to the centre of public media attention. Questions of polyamory have emerged as a major concern within law, social policy, family sociology, and gender and sexuality studies. Yet certain core issues have remained underexplored. This includes the distinctive nature of polyamorous intimacy, the structure of polyamorous household formations, and the dynamics of care work within poly families. In particular, poly parenting has been subject to tabooisation and scandalisation. Governing bodies, the judiciary, and educational institutions have remained largely ignorant of polyamorous relationships. Research documents the exclusions of poly families (and individuals) from access to legal provisions and protections and their common discrimination in the courts, namely, in custody cases. It further highlights the discrimination of poly-identified adolescents in school and college settings and the predicament that poly families face when interacting with public institutions (including schools and kindergartens). Insights into parenting practices and the organisation of childcare are vital for understanding the transformative potential of polyamorous ways of relating. It is also important for challenging the common demonisation and stigmatisation of polyamory within conservative family politics that perceives polyamory exclusively from a harm perspective. This article will review and critically analyse existing research on poly parenting focussing on three dimensions: (a) parenting practices, (b) social and legal discrimination, and (c) parental response to stigmatisation. The article argues for a stronger incorporation of queer perspectives within the guiding frameworks of research into parenting in consensually non-monogamous and polyamorous relationships to highlight the transformative potential of the 'queer bonds' that sustain many of these practices.